Awareness and Attitude regarding Modes of Delivery among Pregnant Women Visiting Antenatal Clinic of University Hospital of Nepal: Cross-sectional Study - Singh, Shreejana; Joshi, Deepak Raj; Parajuli, Bimala; Khatri, Pratima; Shrestha, Bikash; Lawot, Isabel (Nepal Mediciti Medical Journal, 2024)
BACKGROUND The ultimate outcome of a nine-month pregnancy is considered delivery. There are two types of delivery: natural and artificial, also known as spontaneous vaginal delivery and cesarean section (CS), respectively. The purpose of this study was to determine pregnant women’s awareness and attitudes toward modes of delivery when they visited the ANC clinic. METHODS The quantitative descriptive cross-sectional study was conducted among 369 pregnant women visiting the ANC clinic of a university hospital. Non-probability sampling was used for sample determination. An interview technique was used for data collection. RESULTS Among 369 participants’ with an average age of 28.3 ± 4.9 years. The majority (90.2%) agreed with the statement that vaginal delivery is a natural procedure .Moreover, 22.6% agreed that CS is preferable to vaginal delivery, and 37.7% strongly agreed that the mother should have the freedom to perform a caesarean section in her choice. Only about one fifth of the respondent had moderate level of knowledge regarding modes of delivery. The level of knowledge is associated with the level of education (p = 0.020) and the decision-making role of the respondent (p = 0.002) but the attitude is found associated with type of the family (p = 0.037) and no. of ANC visits (p = 0.001) CONCLUSION The participants demonstrated moderate level of knowledge regarding modes of delivery and positive attitude towards normal delivery. Women having the right to make decisions regarding their preferred modes of delivery, including the freedom to choose CS.